Liquid Film Condensation behind Shock Waves on the Cold Wall of a Diaphragmless Vertical Shock Tube: An Experimental Study - H. D. Zhu; X. Chen; M. Y. Zhang; K. D. Yang; P. Lui; M. Wu; C. Ding; D. J. Liu (Journal of Applied Fluid Mechanics, 2022)
The aim of this study was to investigate the condensation of HFC-134a vapor on a shock tube wall behind shock waves. The time-dependent thickness of the condensed liquid film was measured using an optical interference method based on multiple reflections of a laser beam. The condensation on the wall was accompanied by an instantaneous increase in the pressure behind the incident shock wave, and when the reflected shock wave reached the observation window, condensation occurred again. In this experimental study, the characteristics of the diaphragmless vertical shock tube were verified. Reliable experimental data could be obtained using the shock tube. The shock waves could be visualized to study their behaviors in different time periods. The experimental results confirmed the formation of a liquid film on the cold wall of the shock tube after the passing of incident and reflected shock waves, with the liquid film behind the incident shock wave exhibiting a faster formation.